Differences Old Perineal Wound Healing Post Hecting with Anesthesia and Without Anasthesia in Postpartum Mother - Pitri, Zilfi Yola; Lubis, Kholilah; Putri, Fania Anyke (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2025)
The use of anesthesia in suturing perineal tears is a mother's loving care. giving anesthesia before being carried out by all midwives on the grounds that giving anesthesia can slow down wound healing. The purpose of this study was to determine whether there was a difference in post-healing perineal wound healing between mothers who were given anesthesia before perineal suturing and mothers who were not given anesthesia before perineal suturing. The type of research is pre-experimental, intact group comparison research design. The sample in this study was a total of 6 people, the sampling technique used was accidental sampling. Data analysis was carried out using the Independent T statistical test, the study was conducted from March 10-May 10, 2024 at Padang Pariaman Hospital. The results showed that the healing time for wounds using anesthesia was 10 days while the healing time for wounds not using anesthesia was 6 days. The results of the bivariate analysis can be concluded that there is a difference in wound healing between mothers who were given anesthesia before the perineal suturing procedure and mothers who were not given anesthesia before the perineal suturing procedure with a value of P = 0.013 (<0.05). Health workers should improve their skills in obstetrics, especially in handling perineal ruptures so that they can reduce the risk of infection in postpartum mothers.